Na trilha do lh: estratégias pedagógicas para tratar a despalatalização da fala na escrita - Santana, Genelucia Cruz (2023)
This study objectives to investigate 4th grade students’ writing of a public school in Sergipe, the application of the digraph “lh”, regarding the process of depalatalization that occurs in orality, interfering in the students' textual production and implying its exchange for other graphemes. We realized through the analysis of textual productions in the initial phase of this research that the vast majority of students make spelling deviations because they rely on their dialectal variations. With the purpose of finding out if these productions interfered directly on the students' writing and in order to, create an interceptor pedagogical sequence that can solve this sort of error. Carrying out diagnostic tests, analyzing writing and speaking data. And in the end we offer a product replicable called “On the Language Trail: paste or shrink!” which has the goal to raise awareness of the existence of “lh” in writing, as a correlate of other phonemesthat emerge in orality. To support our discussion, we bring authors such as Magda Soares (2020) and Kleiman (2007), who contribute to the areas of literacy and Seara, Nunes and Lazzarotto- Volcão (2019), Cagliari (1974) and Cristófaro-Silva (2007) who teach us about phonetics and phonology. The research results show that in orality the sound of [λ] is often replaced by [l]. Which reflects the most recurrent exchange in the writing of “lh” for “li”. The most frequent pronunciation for the context of the target sound, however, occurs with the realization of [λ] followed by a high front vowel: [λ]. In both cases, we have a process of “iotização”, but onlythe first emerges for writing. We noticed, in lesser occurrences, the exchange of the palatal for a vowel, generating vocalization or semi-vocalization, which is also transposed, in the same proportion for writing. There were rare occurrences of depalatalization by lateralization. In other words, both in the speech and in the students' compositions, that is, the exchange of [λ] for [l]. Regarding textual production, we also recorded some omissions of the “l” and maintenance of the “h”, which can demonstrate that not only orality influences the spelling, but also the lack of skill with graphemes represented by two letters.